Factors Influencing Visual Behaviors among Secondary School Children in Nakhon Hat Yai Municipality, Changwat Songkhla - Chansawang, Wannee; Jittanoon, Piyanuch; Saksorngmuang, Pimpisa (Journal of Health Science of Thailand, 2018)
This descriptive study was aimed at examining the influence of eye health knowledge, visual behavior opinion, family reinforcement, peer reinforcement, and accessing to resources on visual behaviors of secondary school children in Nakhon Hat Yai municipality. The samples consisted of 130 students recruited by systematic random sampling after selecting the schools by simple random sampling. Data were collected, during August to September, 2007, using factor influencing visual behavior questionnaire and were analyzed using percentage, mean, standard deviation and stepwise multiple regression. Results revealed that peer reinforement was the only significant predictor of visual behaviors in secondary students, accounting for 11 percent of explained variance. Findings suggest the need to promote the role of peer group in promoting, supporting and pursuing proper visual behaviors among adolescents.